Cadillac jukebox - Burke, James Lee, 1936- (Burke, James Lee, 1936- Dave Robicheaux novel., 1996)
Aaron Crown comes from a long line of shady Cajun characters, and rumors of Klan ties swirl around his family<U+2014>so his arrest for the murder of a black civil rights leader would seem to be an open and shut case. But when the man who worked hardest to put Crown away ascends to the governor<U+2019>s mansion, detective Dave Robicheaux begins to suspect that Aaron may be innocent of the crime. Soon key figures in high places start pressuring Dave to drop his investigation<U+2026>but that only makes him more determined to uncover the truth at any cost.